Bacillus amyloliquefaciens SC06 Protects Mice Against High-Fat Diet-Induced Obesity and Liver Injury via Regulating Host Metabolism and Gut Microbiota - Wang, Yang; Wu, Yanping; Wang, Baikui; Xu, Han; Mei, Xiaoqiang; Xu, Xiaogang; Zhang, Xiaoping; Ni, Jiajia; Li, Weifen (Frontiers in Microbiology, 2019)
Obesity and the related liver diseases are prevalent around the world. Although probiotics have been shown to prevent obesity through multiple ways, only few researches investigated the lipid-lowering effects of probiotic Bacillus. Moreover, the limited results consistently suggested that Bacillus regulated genes related to lipogenesis and oxidation, but no further exploration was made. Our previous study revealed that Bacillus amyloliquefaciens SC06 has potent antioxidant capacity in vitro. The aim of this study is to investigate the effects of SC06 on obesity and the associated liver injury of high-fat diet (HFD)-fed-mice and its underlying mechanism. By feeding normal chow (NC), NC+SC06, HFD and HFD+SC06 to mice, we found that SC06 improved body weight gain, hepatic steatosis, and glucose metabolism of HFD-mice. Further, SC06 also increased the antioxidant capacity of mice through Nrf2/Keap1 signaling pathway. High-throughput sequencing of 16S rRNA gene showed that HFD changed the gut microbiota dramatically, while HFD+SC06 decreased the ratio of Firmicutes/Bacteroidetes and increased TM7 abundance. More differences were also found in lower taxa. Altogether, SC06 is a potential probiotic that decreases HFD-related lipid accumulation and liver injury via regulating the antioxidant capacity and host gut microbiota.